The “medical” investigation of specific learning disorders - Gordon, Neil (Journal of Pediatric Neurology, 2004)
Specific learning disorders may well be due to loss of neurons in certain parts of the brain, or perhaps more frequently to interruption of circuits connecting one part of the brain with another; so-called non-connection and disconnection syndromes. This paper is concerned with the contribution that medical investigations can make to elucidating the localisation and causes of developmental disabilities of this type, especially of dyslexia and of disorders of language function. Brief descriptions are given of the various techniques that can be employed; and blood flow studies and functional magnetic resonance imaging can be particularly useful in this field. Studies on children with developmental dyslexia are among the most frequent that have been carried out, and some of these are reviewed to show the kind of information that can be acquired. Such tests can not only help in the localisation of function, but also in assessing the results of remedial teaching. Then the investigation of language function is discussed in the same way, and in showing evidence of cerebral plasticity, and in giving a prognosis after vascular lesions for example. Associated disabilities, such as the attention deficit hyperactivity disorder and autism, will obviously have a profound effect on learning, and can also be investigated with these methods. The advent of these techniques holds out great possibilities of increasing our knowledge of specific learning disabilities, and although many of the advances in this field will come from psychologists and teachers, there is no doubt that medicine can make a significant contribution. (J Pediatr Neurol 2004; 2(1): 3–8).
Keywords: specific learning disorders; medical investigations